(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Internet and the use of web sites has grown during the past decade to become more and more important as a marketing communication tool, in today’s rapidly changing business environment. Furthermore it is also an important source of income. This Paper aims to investigate how web sites are used as an integrated marketing communications tool regarding issues such as objectives, reaching and communicating with target audiences, what types of integrated marketing communication tools used and how to measure the effectiveness of using web sites as an integrated marketing communications tool.